STRENGTH STUDY OF MACHINE TOOL BEDS WITH CURVILINEAR STIFFENERS FROM POLYMER CONCRETE - Berg, Alexandra; Nurzhanova, Oxana; Berg, Andrey; Zharkevich, Olga; Nikonova, Tatyana; Yurchenko, Vassiliy; Taimanova, Gulnara (Journal of Applied Engineering Science, 2024)
This study addresses enhancing the strength of metal-cutting machine tool beds made from polymer concrete by optimizing the internal cross-section design through spiral stiffeners. Key factors influencing the bed’s strength include the composite preparation technology, the mixing speed (600 - 800 rpm), and duration (3 - 4 minutes). A strong correlation exists between spiral pitch, mixing speed, mixing time, and the bed’s strength.